Insulin-resistance and lipids metabolism in women at menopause - Gresko, Marina Dmitrуina; Bulik, Tatyana Sergуivna; Rynzhuk, Larisa Vasylivna; Rynzhuk, Vasyl Yefremovych; Palamariuk, Olexandra Ahdriivna; Vovk, Olesia Yuriivna (Journal of Education, Health and Sport, 2018)
The article describes lipid metabolism in women during premenopausal and considered their relationship with the level of insulin sensitivity and abdominal obesity. Examined 20 women aged 46-48 years, with fixed transition to pre-menopause on the bases of menstrual cycle dysfunction or amenorrhea during a year as well as a decrease of visualized follicular reserve according to the results of ultrasonic examination of the organs of the small pelvis, were involved into investigation. Body mass increase with abdominal obese formation and disorders of the lipid metabolism against a background of insulin resistance is observed in women during pre-menopause against a background of sexual hormones deficiency.